“ANALISA HUKUM ATAS SENGKETA KEPEMILIKAN TANAH KAVLINGAN MILIK KELOMPOK PEGAWAI PENSIUNAN DEPARTEMEN KEHUTANAN DI KABUPATEN KAMPAR” - HENI FITRIA (PREMISE LAW JURNAL, 2017)
Land plots can be one of land disputes because of rapid development of an area so that its sales value will be high. Therefore, if a person wants to buy a plot of land, he has to find out its physical condition, ownership status, and other important documents, and the most important thing is that it is free from dispute.[1] Land title transfer should be made in authentic certificate before a PPAT (official empowered to draw up land deeds). It has to contain the facts and it has to be registered. The validity of legal basis on land certificate is basically the same as land registration. Therefore, the aim of land registration, which used to follow Article 19, paragraph 1 of the Land Act, was merely to guarantee legal certainty. However, based on Article 3 of the Government Regulation No. 24/1997 the purpose of land registration was broadened by settling dispute in the ownership of land plots owned by groups of retired employees of the Department of Forestry in Kampar Regency. Keywords: Land Plots, Dispute, Retired Employees of Department of Forestry, Kampar [1] Badriyah Harun, Solusi Sengketa Tanah dan Bangunan, (Yogyakarta: Pustaka Yustisia, 2013), hlm 101